Re-engineering the financial services sector for stability : papers & proceedings of the '95 bank directors' seminar - Financial Institutions Training Centre (Nigeria Financial Institutions Training Centre, 1995)
This book is a collection of the papers presented at the eleventh Annual Bank Director's seminar organized by the Financial Institutions Training Centre towards the re-engineering of the Nigerian financial services sector for stability.
Papers & proceedings of the '95 bank directors' seminar
Includes bibliographical references
rua 31/08/16, aia 09/09/16
Loans
Keywords: Banks and banking; Financial institutions; Financial services industry; Nigeria